Switching of OAS1 splicing isoforms overcomes SNP-derived vulnerability to SARS-CoV-2 infection - Kei Iida; Masahiko Ajiro; Akiko Nakano-Kobayashi; Yukiko Muramoto; Toru Takenaga; Masatsugu Denawa; Ryo Kurosawa; Takeshi Noda; Masatoshi Hagiwara (BMC Biology)
Abstract Background The SARS-CoV-2 pandemic provided important insights into the relationship between infectious diseases and the human genome. A genomic region encoding the 2′-5′-oligoadenylate synthetase (OAS) family proteins that sense viral genomic RNAs and trigger an antiviral response contains single nucleotide polymorphisms (SNPs) associated with SARS-CoV-2 infection susceptibility. A high-risk SNP identified at the splice acceptor site of OAS1 exon 6—a terminal exon—alters the proportion of various splicing isoforms of OAS1 and its activity. However, the actual causality of this SNP or splicing to infection susceptibility remains unknown. Results In this study, it was found that serine–arginine-rich splicing factor 6 (SRSF6) binds to the splice donor site of the human OAS1 exon 5. SRSF6 determines the selected alternative terminal exon when the risk allele disrupts the splice acceptor site. Subsequently, an inhibitor for CDC-like kinase was rationally selected as a candidate splicing modulator. RNA-Seq and RT-PCR analyses revealed that this inhibitor can induce splice switching of OAS1 mRNAs in the human lung adenocarcinoma cell line Calu-3. Under the inhibitor treatment, the cells exhibited reduced SARS-CoV-2 infection rates. Meanwhile, the colonic epithelial cell line Caco-2 expressed non-risk type OAS1 mRNA isoforms that did not undergo splice-switching or demonstrate altered SARS-CoV-2 sensitivity following treatment with the inhibitor. Conclusions These results indicate that a high-risk SNP in OAS1 influences cell susceptibility to SARS-CoV-2 infection by inducing splice-switching at its terminal exon. Additionally, chemical splicing modifiers may prove beneficial in overcoming this genomic vulnerability.